HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT STRES MAHASISWA YANG MENGIKUTI PEMBELAJARAN ONLINE - Janeri Katimpale; Ferdinand Wowiling; Andi Buanasari (Universitas Sam Ratulangi, 2022)
Background: Stress is a normal reaction to various pressures experienced by each individual, children, adolescents, and adults, including students. In dealing with stress, students need family support in reducing the level of their stress. Aim: The purpose of the study was to determine the relationship between family support and stress levels of students who took online learning at PSIK FK Unsrat Manado. Methods: this research used a quantitative research design with a cross sectional approach. There were 116 students who take online learning at PSIK FK Unsrat Manado involved in this study. The instruments in this study used a Depression Anxiety and Stress Scale 42 (DASS 42) questionnaire and a Family Support questionnaire. The results of the statistical test using the Pearson Chi Square test at a significance level ofÂ 95%, showed a significant value value = 0.005 < (0.05), this shows that there is a significant relationship between the two variables. Conclusion: There was a significant relationship between family support and the stress level of students who took online learning at PSIK FK Unsrat Manado. Keywords: Family Support; Stress Level; Online Learning